The Muslim Culinary in Ho Chi Minh City: Production and Consumption Against the Backdrop of Tourism - Phan, Tu Anh (Islamic Studies, 2024)
Ḥalāl food is a common feature in Muslim lives across the world. In Muslim quarters of Ho Chi Minh City, Vietnam, locally-made food products are self-recognized as ḥalāl by the community. Ḥalāl food self-recognition is a tradition that exists within closed Muslim communities based on a process of production and consumption standardized by Muslims alone. However, the urban culinary scene has changed as the Vietnamese government issued policies for enhancing the tourism industry and exhorting Muslim enterprises to produce their typical local products. Using qualitative research methods in combination with document analysis, this article shows the sophisticated and varied culinary trade techniques of the Muslim market in Ho Chi Minh City and Southern Vietnam. Products that are not ḥalāl or that falsely claim to be ḥalāl have been introduced to the market. As a result, the involvement of the local Muslim community in the manufacturing process of these ḥalāl-standardized goods is analysed and examined to prevent the products from falsely claiming to be ḥalāl as well. Cultural aspects of the local Muslim community in food processing of ḥalāl products are often applied in creating tourist products in Muslim neighbourhoods. This research also argues that the market economy in Vietnam brings profits for the country, yet is also challenging for Muslims to produce and consume ḥalāl food.